The cats in Krasinski Square - Hesse, Karen (Scholastic Press, 2004)
Two Jewish sisters, escapees of the infamous Warsaw ghetto, devise a plan to thwart an attempt by the Gestapo to intercept food bound for starving people behind the dark Wall.